2020
DOI: 10.4236/ojmn.2020.102030
|View full text |Cite
|
Sign up to set email alerts
|

White Cord Syndrome: The Terrible Nightmare

Abstract: Introduction: Reperfusion injury of spinal cord "white cord syndrome" refers to acute neurological deterioration after decompressive spinal surgery without any reported intraoperative events. The postoperative appearance of diffuse hyperintense intramedullary areas in T2-weighted MRI is characteristic without any other pathological or compressive signs. The etiology may be due to sudden expansion of the cord after reperfusion of chronically ischemic areas leading to disruption of blood-spinal cord barrier. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…5 Prior literature have shown that the various causes for cord compression included focal disc herniation with canal stenosis, other acquired causes like arachnoid cyst and even mass lesions such as metastasis involving vertebra. 6 In our patient, primary pathology was an osteochondroma at cervicodorsal junction causing cord compression.…”
Section: Discussionmentioning
confidence: 66%
“…5 Prior literature have shown that the various causes for cord compression included focal disc herniation with canal stenosis, other acquired causes like arachnoid cyst and even mass lesions such as metastasis involving vertebra. 6 In our patient, primary pathology was an osteochondroma at cervicodorsal junction causing cord compression.…”
Section: Discussionmentioning
confidence: 66%